Jupiter radio emission probability tool - Cecconi, B.; Aicardi, S.; Lamy, L. (Frontiers in Astronomy and Space Sciences, 2023)
Jupiter is a source of intense radio emissions in the decametric wavelength range observable from ground (above ~10 MHz) and from space (down to a few kHz). The strong anisotropy of the Jovian radio sources results in characteristic shapes in the temporal-spectral domain, which can be used to identified the various types of Jovian radio components. The Jupiter Probability Tool provides users with Jovian radio emission observability predictions, depending on the observers location, and the radio emission class. The application can be used for observation planning or data analysis for ground or space observations.